2014
DOI: 10.1186/1471-2377-14-65
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the first dose of fingolimod for multiple sclerosis: results of an open-label clinical trial

Abstract: BackgroundIn patients with relapsing-remitting MS (RRMS) fingolimod prevents disease relapses and delays disability progression. First dose administration of fingolimod is associated with a transient, dose-dependent decrease in heart rate (HR) in the 6 hours after drug intake.The aim of the study is to to assess safety and tolerability of the first dose of fingolimod in a cohort of Italian patients with RRMS without alternative therapeutic options.MethodsOpen-label, single arm, multicentre study. After the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 10 publications
3
40
0
Order By: Relevance
“…The most common AE were cardiovascular events, including bradycardia and first‐degree or second‐degree atrioventricular block, after administration of the first dose 12. These AE usually occur within 1 h after administration of the drug, and bradycardia usually lasts for several days.…”
Section: Safety Profile Of Fingolimod Therapymentioning
confidence: 99%
“…The most common AE were cardiovascular events, including bradycardia and first‐degree or second‐degree atrioventricular block, after administration of the first dose 12. These AE usually occur within 1 h after administration of the drug, and bradycardia usually lasts for several days.…”
Section: Safety Profile Of Fingolimod Therapymentioning
confidence: 99%
“…As yet, there has been no report on the safety of the first dose of fingolimod in Brazilian patients with MS where the protocol recommends medical observation and cardiovascular monitoring for at least six hours. In fact, except for results on clinical trials with very strict inclusion criteria for patients 4 , there are few reports on the real life experience with the first dose of fingolimod 2,5 . Retrospective data were collected for 180 patients aged over 18 years diagnosed with MS according to the revised McDonald criteria 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The study of Ontaneda et al which dealt with clinical practice data also demonstrated 1% rate of bradycardia as a complication of fingolimod initiation 2 . A recent Italian study reported 2% cardiovascular adverse events in patients taking the first dose of fingolimod, mainly bradycardia and atrio-ventricular block 5 . The Italian study used a method similar to ours, reporting the results of daily medical practices.…”
Section: Introductionmentioning
confidence: 99%
“…S1P receptors are expressed in many body tissues, explaining a number of unwarranted effects of fingolimod. After the first dose of fingolimod, bradycardia and atrioventricular conduction block have been reported in fewer than 2 % of patients [31][32][33]. Other side effects are macula oedema, elevated liver function tests, an increased risk of infections (fatal herpes virus in a few cases) and hypertension [31,32].…”
Section: Second-line Disease-modifying Drugsmentioning
confidence: 97%